FROM REAL TO DIGITAL–MEDIATED OBJECTS: SOME REFLECTIONS UPON THE DIGITAL REPRODUCTION OF ARCHAEOLOGICAL OBJECTS - Christos Merantzas (European Scientific Journal, ESJ, 2014)
The digital duplication proposed by computer–mediated technologies (CMT) cultivates a new aesthetics of reproduction as it serves the need for persistence of the object, thus, ensuring its ephemeral presence. The digital object, in turn, appears not to be present to us immediately, but through its digital model. Nevertheless, the question to pose is whether the reality of the object, not in its immediacy, but in the perspective of its perpetuation in time ultimately leads to its replacement by an artificial integrity that challenges the risks of actual existence. A possible answer could be that the denaturalization of the object present to our consciousness denies its right to exist in the corruptible historical time in order to conquer digital oblivion.